2005
DOI: 10.1309/un1aq2wju9hdd72f
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid Hyperplasia With Eosinophilia (Epithelioid Hemangioma) of the Lung

Abstract: Two cases of primary angiolymphoid hyperplasia with eosinophilia (epithelioid hemangioma) (ALHE/EH) of the lung are described. Both patients are white, a 60-year-old man and a 27-year-old woman. One patient had a long-standing history of asthma, and the other had symptomatology related to the pulmonary mass. Wedge resections were performed in both cases, and both lesions shared similar histopathologic changes, mainly the presence of a tumor mass with a marked presence of eosinophils in the background, lymphoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A relationship between ALHE with asthma is not clear. Moran et al (2005) 7 reported two ALHE (EH) cases affecting the lung; of them, only one patient had a long-standing history of asthma 7 . Differently, Galindo-Ferreiro et al (2016) 8 assessed ALHE cases with orbital and adnexal involvement, and none of them had asthma 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between ALHE with asthma is not clear. Moran et al (2005) 7 reported two ALHE (EH) cases affecting the lung; of them, only one patient had a long-standing history of asthma 7 . Differently, Galindo-Ferreiro et al (2016) 8 assessed ALHE cases with orbital and adnexal involvement, and none of them had asthma 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The reactive blood vessels are often epithelioid, leading to the terms "histiocytoid" or, more recently "epithelioid" haemangioma [6]. Immunohistochemical stains usually show a major population of T-Lymphocytes [5] with occasional B cells forming lymphoid follicles [6]. Since the description of the initial large series [6], there have been numerous reports of this condition, with lesions occurring in a variety of organs, including disseminated disease [1,[9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…It is rare in elderly patients and in the non-Asian paediatric population. ALHE is somewhat more common in females; however, a male predominance has been noted in selected Asian studies [5]. It presents most commonly in patients aged 20 -50 years, with a mean onset of 30 -33 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…ALHE and KD both rarely involve visceral organs including lungs, spleen, and liver. [12][13][14][15] KD in particular is associated with proteinuria and nephrotic syndrome. 16 The differential diagnosis of KD and ALHE with multisystem involvement includes IgG4-RD.…”
Section: Introductionmentioning
confidence: 99%